Changes in zircon chemistry during archean UHT metamorphism in the Napier complex, Antarctica - Kusiak, M.; Whitehouse, M.; Wilde, Simon; Dunkley, Daniel; Menneken, M.; Nemchin, Alexander; Clark, Christopher (American Journal of Science, 2013)
Zircons from two paragneisses (from Mount Sones and Dallwitz Nunatak) and one orthogneiss (from Gage Ridge) in the Tula Mountains, Napier Complex (East Antarctica) were analyzed for U-Pb age, oxygen isotopes, REEs and by scanning ion imaging. A large number of zircons from all samples are reversely discordant. Mount Sones zircons show an age range from 3.0 Ga to 2.5 Ga and underwent high-grade metamorphism at both ~2.8 Ga and 2.5 Ga. Zircons from Dallwitz Nunatak record detrital ages between 3.5 Ga and 2.5 Ga. Zircons from Gage Ridge record multiple age groups, with concordant data between 3.6 Ga and 3.3 Ga and reversely discordant data that form a discrete ~3.8 Ga population. All of the grains show evidence of Pb mobility during metamorphism. Ion imaging of zircons reveals Y and U zonation, characteristic of magmatic zircon, together with a micro-scale patchy distribution of 206Pb and 207Pb that does not correspond to either growth zonation or crystal imperfections. Some of these patches yield 207Pb/206Pb ages >4 Ga, whereas others yield ages younger than the magmatic crystallization age. Reversely discordant data are the result of ancient Pb mobilization, which is independent of the degree of metamictisation, oxygen isotope and REE content of the zircons. This mobilization can result in spurious ages and was most likely caused by polymetamorphism under anhydrous conditions; that is two high-grade events; one poorly defined at ~2.8 Ga and the other ultra-high temperature (UHT) metamorphism at 2.5 Ga.